2007
DOI: 10.1164/rccm.200612-1803oc
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Heparin in Patients with Severe Sepsis Treated with Drotrecogin Alfa (Activated)

Abstract: Compared with placebo, concomitant prophylactic heparin was not equivalent, did not increase 28-day mortality, and had an acceptable safety profile in patients with severe sepsis receiving DrotAA. Heparin discontinuation should be carefully weighed in patients considered for DrotAA treatment. XPRESS clinical trial registered with www.clinicaltrials.gov (NCT 00049777). The study ID numbers are 6743; F1K-MC-EVBR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(95 citation statements)
references
References 35 publications
5
82
0
2
Order By: Relevance
“…Data in support of pharmacologic prophylaxis are considered somewhat indirect. Except for a large prospective randomized controlled trial comparing VTE in septic patients treated with drotrecogin alfa who were randomized to receive placebo versus UFH versus LWMH [515], all studies have been in an undifferentiated population of critically ill patients. Overall, we made a strong recommendation in favor of pharmacologic prophylaxis against VTE in critically ill patients based on the overall efficacy of this intervention, although the evidence was downgraded to moderate because of indirectness of the populations studied.…”
Section: We Suggest Mechanical Vte Prophylaxis When Pharmacologic Vtementioning
confidence: 99%
See 1 more Smart Citation
“…Data in support of pharmacologic prophylaxis are considered somewhat indirect. Except for a large prospective randomized controlled trial comparing VTE in septic patients treated with drotrecogin alfa who were randomized to receive placebo versus UFH versus LWMH [515], all studies have been in an undifferentiated population of critically ill patients. Overall, we made a strong recommendation in favor of pharmacologic prophylaxis against VTE in critically ill patients based on the overall efficacy of this intervention, although the evidence was downgraded to moderate because of indirectness of the populations studied.…”
Section: We Suggest Mechanical Vte Prophylaxis When Pharmacologic Vtementioning
confidence: 99%
“…In those trials evaluating PE, the rates were significantly lower in patients receiving LWMH. As with all studies of pharmacologic VTE prophylaxis, only one trial [515] was restricted to septic patients, and that trial utilized drotrecogin alfa in all patients. An additional meta-analysis found that LWMH was more effective than UFH in reducing the incidence of DVT and PE in critically ill patients [516].…”
Section: We Suggest Mechanical Vte Prophylaxis When Pharmacologic Vtementioning
confidence: 99%
“…However, the incidence of ischemic stroke was lower (0.3 vs. 1.3%). Simultaneous administration of heparin did not influence the effect of drotrecogin alfa (activated), based on mortality rates in both groups (28.3% with heparin vs. 31.9% without heparin) [36].…”
Section: Dosage Mode Of Administrationmentioning
confidence: 93%
“…Also, the safety of heparin treatment is debatable in DIC patients who are prone to bleeding. A large trial in patients with severe sepsis showed a slight, but nonsignifi cant benefi t, of low dose heparin on 28-day mortality in patients with severe sepsis and no major safety concerns [ 29 ].…”
Section: Anticoagulant Treatmentmentioning
confidence: 99%